Trio: An Emerging Model of Adult Professional Learning - Barry Shekley; Marijke Kehrhahn; Sandy Bell; Robin Grenier (Adult Education Research Conference, 2008)
Based on research conducted over the past 6 years, the authors offer a model that depicts the key features of professional learning. The model is based on the proposition that optimal professional learning is possible when specific individual attributes, environmental affordances, and key experiences intersect.
Keywords: professional development; workplace learning